PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK, KAITANNYA DENGAN PERFORMANSI PESRTA DIDIK - Rangkuti, Ahmad Nizar (IAIN PADANGSIDIMPUAN, 2016)
This research is motivated by the lack of learner’s performance in mathematics learning process, especially class III’s students of SDN 200 306 Batunadua Padangsidimpuan. The purpose of this study was to find out how the performance of learners with a realistic mathematics education approaches. This research is a descriptive study. Based on data analysis found that the performance of learners that includes confidence, reasoning, activity, creativity, and motivation of learners very well after applying realistic mathematics education approach.